Methods and compositions for the prevention of opiate tolerance using mitragynine. - Fakurazi, Sharida; Baharuldin, Mohamad Taufik Hidayat; Mohd Moklas, Mohamad Aris; Ithnin, Hairuszah; Abd Rahman, Shamima (2011)
The present invention relates to methods and compositions to counter the side effects of analgesic treatments with opioids such as morphine. Provided are novel treatment regimes comprising the administration of mitragynine for the prevention, reversal and/or delay of the progression and/or development of a tolerance of a subject against the pharmaceutical effects of an opiate. Also comprised by the present invention are therapeutic means for the treatment of severe or chronic pain using a combination of mitragynine and opiates, as well as pharmaceutical compositions comprising the compounds of the present invention.